2016
DOI: 10.1589/jpts.28.2123
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of isometric muscle strength measurements of hip abduction and abduction with external hip rotation in a bent-hip position using a handheld dynamometer with a belt

Abstract: [Purpose] This study aimed to investigate the relatedness, reliability, and validity of isometric muscle strength measurements of hip abduction and abduction with an external hip rotation in a bent-hip position using a handheld dynamometer with a belt. [Subjects and Methods] Twenty healthy young adults, with a mean age of 21.5 ± 0.6 years were included. Isometric hip muscle strength in the subjects’ right legs was measured under two posture positions using two devices: a handheld dynamometer with a belt and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
4
18
1
Order By: Relevance
“…The test-retest reliability of HHD-technique 2 (ICC3.1 agreement 0.96–0.97) was similar as previously reported HHD test-retest reliability (ICC 0.74–0.98) [ 17 , 22 , 24 , 25 ] and intra-rater reliability (ICC 0.81–0.96) [ 18 21 , 26 , 27 ] of hip abduction strength measurements. The inter-rater reliability of HHD-technique 2 (ICC2.1 agreement 0.92) was better than outcomes reported in previous studies (ICC 0.58–0.88) [ 18 , 20 , 23 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The test-retest reliability of HHD-technique 2 (ICC3.1 agreement 0.96–0.97) was similar as previously reported HHD test-retest reliability (ICC 0.74–0.98) [ 17 , 22 , 24 , 25 ] and intra-rater reliability (ICC 0.81–0.96) [ 18 21 , 26 , 27 ] of hip abduction strength measurements. The inter-rater reliability of HHD-technique 2 (ICC2.1 agreement 0.92) was better than outcomes reported in previous studies (ICC 0.58–0.88) [ 18 , 20 , 23 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 87%
“…Aramaki et al [17] found a Pearson’s correlation coefficient of 0.82 in healthy young adults. Hebert et al [18] found an ICC3.1 of 0.69 in healthy adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Handheld dynamometry (HHD) is another reliable and valid measure that allows quantification of manual muscle tests. [37][38][39][40][41] The relatively low cost and ease of use offers a more efficient manner to collect force data in a clinical setting. Both of the aforementioned methods assess force in nonweight-bearing positions in a single plane of motion to despite the fact that during weightbearing, hip muscles are responsible for postural and pelvic stability in addition to simply moving the legs.…”
Section: Introductionmentioning
confidence: 99%